2013
DOI: 10.4238/2013.march.11.21
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of phylogenetic relationship of rare plant species collected from Saudi Arabia using internal transcribed spacer sequences of nuclear ribosomal DNA

Abstract: ABSTRACT.The rare and endangered plants of any country are important genetic resources that often require urgent conservation measures. Assessment of phylogenetic relationships and evaluation of genetic diversity is very important prior to implementation of conservation strategies for saving rare and endangered plant species. We used internal transcribed spacer sequences of nuclear ribosomal DNA for the evaluation of sequence identity from the available taxa in the GenBank database by using the Basic Local Ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…The study revealed a high level of genetic diversity among the Ajuga arabica populations in Saudi Arabia. This finding is consistent with previous studies on other plant species in Saudi Arabia, which have also reported high levels of genetic diversity (Al-Qurainy et al, 2013;Al-Rashedi et al, 2018). The high genetic diversity of Ajuga arabica populations in Saudi Arabia can be attributed to a number of factors, including its geographical location, climatic conditions, and historical events.…”
Section: Discussionsupporting
confidence: 93%
“…The study revealed a high level of genetic diversity among the Ajuga arabica populations in Saudi Arabia. This finding is consistent with previous studies on other plant species in Saudi Arabia, which have also reported high levels of genetic diversity (Al-Qurainy et al, 2013;Al-Rashedi et al, 2018). The high genetic diversity of Ajuga arabica populations in Saudi Arabia can be attributed to a number of factors, including its geographical location, climatic conditions, and historical events.…”
Section: Discussionsupporting
confidence: 93%
“…The ITS markers have already been used successfully for identification of Ochradenus arabicus (Resedaceae), an endemic medicinal plant of Saudi Arabia (Khan et al, 2012). Similarly, phylogenetic relationship was worked out using the nrDNA-ITS sequence in Senecio asirensis, Nepeta deflersiana and some rare species of Saudi Arabia (Khan et al, 2013;Al-Qurainy et al, 2013;. The development of ITS marker is easy, reproducible and can be developed from a small amount of tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Results revealed the proximity and maximal identity of Resedae with 100% bootstrap support and nested within the clade. Al-Qurainy et al (2013, 2014a,b) analyzed five species of rare and endangered plants from Saudi Arabia. Al-Qurainy et al (2014a,b) evaluated medicinal plants Nepeta deflersiana and Plectranthus asirensi using DNA barcoding.…”
Section: Plant Dna Barcoding: An Emerging Approachmentioning
confidence: 99%